2002
DOI: 10.1002/ijc.10590
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 c‐160a promotor polymorphism is not associated with risk of stomach cancer

Abstract: We have combined data from case control studies designed to test the hypothesis that the c-160a promotor polymorphism in the gene coding for the cell adhesion molecule E-cadherin (CDH1) is associated with stomach cancer. A total of 899 individuals (433 patients and 466 controls) were analyzed. The genotype frequencies did not differ significantly between cases and controls, and the genotype-specific risks were not significantly different from unity, with an odds ratio for heterozygotes compared with the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
32
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 5 publications
9
32
0
Order By: Relevance
“…In contrast, Humar et al [34] described the association of the mutant A allele with sporadic diffuse gastric cancer in Italy. No association was found between À160C/A genotype and risk of stomach cancer in three populations of European origin, namely Canadians, Germans, and Portuguese [31]. In urothelial cancer, however, Japanese individuals carrying the AA genotype had a 2.3-fold increased risk of being affected by the disease than CC individuals, although no correlation with tumor progression was detected [32].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In contrast, Humar et al [34] described the association of the mutant A allele with sporadic diffuse gastric cancer in Italy. No association was found between À160C/A genotype and risk of stomach cancer in three populations of European origin, namely Canadians, Germans, and Portuguese [31]. In urothelial cancer, however, Japanese individuals carrying the AA genotype had a 2.3-fold increased risk of being affected by the disease than CC individuals, although no correlation with tumor progression was detected [32].…”
Section: Discussionsupporting
confidence: 46%
“…The association among Jamaicans should be considered with caution since IVS1 þ 6T/C was noticeably out of Hardy-Weinberg equilibrium. The frequency of the A allele in European American controls was lower than that reported for most European populations in other PCA studies [16][17][18] or non-PCA studies [31,34], but was comparable to Japanese population frequencies [20,32]. With the exception of SNP À160C/A, we found significant differences between ethnicities in genotype and allele frequencies of all CDH1 markers.…”
Section: Discussionsupporting
confidence: 45%
“…Thus, A-type promoter variant may be regarded as a candidate cancer susceptibility polymorphism. However, recent epidemiological studies failed to demonstrate a correlation between the E-cadherin promoter variant and breast (19) or colorectal cancer (20) or gastric cancer (15). In the present study, there is no significant difference in the Ecadherin -160 promoter genotype between normal healthy individuals and gastric cancer patients (Table 1).…”
Section: Discussionsupporting
confidence: 46%
“…However, It has been reported that the A allele was suggested to be protective against gastric cancer in Taiwanese (14) and that the -160 promoter polymorphism is not associated with risk of gastric cancer (15). Thus, it is worthwhile to investigate the genotype specific risk of -160 promoter polymorphism in Korean gastric cancer patients.…”
Section: Introductionsupporting
confidence: 41%
“…4,5 An open question remains the inverse relation (AA as protective or risk genotype) between cancer and controls comparing PCa (the study of Verhage et al 1 and our study) and gastric cancer studies. 5,6 The TaqMan assay on demand proved robust and useful. It allowed easy determination of the alleles and it saved the considerable amount of time normally required to set up the assay because the only variable that needs to be adjusted is the amount of DNA that is allowed for in broad boundaries.…”
mentioning
confidence: 99%